PUBLIC POLICY AND THE CHALLENGES OF RURAL DEVELOPMENT IN NIGERIA - OMINI UBI UBI; ARCHIBONG MAURICE EFFIOM (International Studies Journal)
This article is on public policy and the challenges of rural development. In recent times rural areas in Nigeria is characterized with myriads of challenges limiting the areas from developing. Strange challenges like terrorism and banditry have cost lives and properties with rural unemployment and poverty. To address these challenges, purposive public policy needs to be formulated and implemented in line with robust third tier of government. The structural functionalism theory was adopted to explain the research article. Qualitative research anchored on secondary sources was used. The article recommended that, States and Federal Government should allow local government to operate full autonomy, involvement of the rural populace in policy decisions and the accountability of political leadership in local government administration.